ECG-gated multislice Computed Tomography angiography as a comprehensive non-invasive imaging tool in patient with aortic coarctation: CTA in aortic coarctation - Runza, Giuseppe; La Grutta, Ludovico; Maffei, Erica; Punzo, Bruna; Cavaliere, Carlo; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2021)
We describe a case of a 52 year-old-woman with aortic coarctation demonstrated by means of 40-slice MSCT angiography. Based on the information extracted from MSCT it was possible to display the anatomical configuration of the disease, the thoraco-abdominal collateral pathways. The best therapeutic approach was established on the basis of MSCT findings. MSCT is a reliable and comprehensive tool for the assessment of adult patients with aortic coarctation.